P-339 Fertility outcomes after laparoscopic bladder endometriosis excision using a CO2 laser: 20-year retrospective analysis in an expert center. (30th June 2022) - Soares, M; Maillard, C; Laurent, P; Jadoul, P; Dolmans, M.M; Gerday, A; Squifflet, J; Luyckx, M
Abstract: Study question: To evaluate fertility outcomes after laparoscopic bladder endometriosis (BE) excision in patients presenting with a post operative pregnancy wish or pre-operative infertility. Summary answer: Surgical excision of BE is followed by high pregnancy rates, with a significant proportion of spontaneous conceptions, even in the infertile population prior to surgery. What is known already: There are currently no guidelines/consensus concerning management of BE in case of infertility( ART? surgery?) and the impact of BE excision on fertility is still not known. Most publications reporting surgical management of BE include patients with different endometriosis types with a very small number of cases of isolated BE, making it difficult to draw conclusions. Study design, size, duration: This is a retrospective, unicentric cohort study conducted at Saint Luc University Hospital Brussels, a tertiary referral center for endometriosis. A total number of 207 patients having undergone laparoscopic bladder endometriosis excision using a CO2 laser between January 1998 and December 2018 were included. Only patients having histologically confirmed endometriosis infiltration of the detrusor muscle were included. Patients with small nodular lesions < 5mm or superficial peritoneal endometrial lesions in the vesico-uterine fold were excluded. Participants/materials, setting, methods: Laparoscopic BE excision was performed by 3 senior surgeons of the team, either with bladder mucosae opening (partial cystectomy) or partial thickness excision ("bladder shaving") technique. Pregnancy and live birth rates according to prior infertility, conception mode and time to pregnancy were recorded. Primary outcome was postoperative pregnancy rate (PR). Secondary outcomes were conception mode and time to pregnancy. Patients with minimum 1-year follow up (FU) after surgery were included for fertility analysis. Main results and the role of chance: Forty-three patients had isolated BE, while BE was associated with other forms of endometriosis in 164 cases, including 50.2% posterior DIE. Among the 176 patients having a minimum 1y FU, mean FU was 7.05 (±4.65)y. Overall, PR among the hundred patients with a postoperative pregnancy wish was 75.8% (100/132): 49 natural conceptions and 51 following ART. Indication for ART were failed natural conception (24/51, 47.1%) or assosiated other cause of infertility (severe male factor, hormonal or tubal) requiring immediate IVF (27/51, 52.9%). PR (81.0% vs 74.8%, p = 0.545) and need for IVF (41.2% vs 53%, p = 0.374) did not statistically differ between patients with isolated or assosiated BE. Total live birth rate was 69.7%. In patients presenting with preoperative infertility, overall PR was 74.5% with 50% natural pregnancies. In the isolated BE group (n = 11) PR was 81.8% with 55.5% (5/9) natural pregnancies and 44.5% needing ART. No statistical difference were found in PR and need for IVF between the isolated and associated BE group. Most pregnancies occured in the first 2 years following surgery. Overall cumulative PR was 42% at 1 year, 65% at 2 years and 75% at 5 years respectively with similar distributions in the isolated and associated BE groups. Limitations, reasons for caution: The main limitation is the retrospective nature of the study, making it difficult to exclude biases. Sample size also remains limited due to the rare incidence of BE, particularly concerning the isolated forms. Wider implications of the findings: This is the largest reported series of patients treated surgically for BE. Fertility results are excellent for an endometriotic population and BE excision seems to have a positive impact, at least in case of natural conception. First-line surgery may be considered in patients with bladder endometriosis having a pregnancy wish. Trial registration number: not applicable